An early venous abnormality: a potential cause of arteriovenous malformation recurrence. (11th September 2012) - Weingarten, David; Pakbaz, Sean; Cho, Aaron; U, Hoi Sang
Abstract : In adults, complete surgical resection of arteriovenous malformations (AVMs) is generally curative. Recurrence of AVMs is extremely rare and most often delayed over many years. The authors report the case of a man in his 20s with rapid AVM recurrence and dual blood supply from the dura and intracerebral vessels. Early recurrence of the AVM allowed documentation of the early events associated with this recurrence. This was evidenced by the first appearance of an early vein without any signs of abnormal vasculature, suggesting that abnormality of the venous drainage system might be an inciting event in the recurrence and perhaps genesis of AVMs.